VIABILITAS BENIH KEDELAI (Glycine max [L.] Merril) SEJALAN DENGAN PENYIMPANAN ALAMIAH DAN PENGUSANGAN CEPAT DENGAN ETANOL - Eko Pramono; M. Syamsoel Hadi; M. Kamal (Universitas Lampung, 2020)
Storing seeds always causes deterioration, mainly due to the long storage time and rapid aging treatment using ethanol. This study aimed to compare the viability of soybean seeds due to the natural storage period and due to accelerated aging with ethanol. The lot of Argomulyo soybean seeds was divided into five subloties. Sublot-1 was the soybean seeds given a natural storage under temperature of ± 26 ºC for 12 months. Sublot-2 was the soybean seeds given a natural storage under temperature of ± 18 ºC for 12 months. Sublot-3 was the soybean seeds applicated with the treatments of the absorption period 0-12 hours to ethanol solution of 8 % (LPLE8). Sublot-4 was soybean seeds applicated with the treatments of the exposure periods 0-180 minutes to saturated ethanol 96% vapour (LDUJE). Sublot-5 was soybean seeds applicated with the treatments of imbibition periods 0-24 hours prior to be exposured on saturated 96% ethanol vapour for 40 minutes (LIPPC). The main variable observed was the percentage of normal seedlings (PKN). The rate of decline in the viability of soybean seeds during storage of 0-12 months under the storage room temperature of 26 C or 18 C respectively a) was greater than that treated with ethanol-8% absorption period of 0-12 hours, and b) did not differ from those treated with 96% 0-180 minutes ethanol saturated vapor treatment period and treated with 0-24 hour imbibition period before exposure to 96% ethanol saturated vapor for 40 minutes. Keywords: Aging, ethanol, normal seedling, seed viability, storage